Derivatives and Inverses!

Calculus Level 3

If b > 0 , f ( x ) = a x b , f ( x ) = f 1 ( x ) b > 0, \:\, f(x) = ax^{b}, \:\ f'(x) = f^{-1}(x) and A A is the area of the region R R bounded by f ( x ) f(x) and f 1 ( x ) f^{-1}(x) , find f 1 ( ϕ ) A f^{-1}(\phi) - A , where ϕ \phi is the golden ratio.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rocco Dalto
Apr 5, 2020

f ( x ) = a x b f ( x ) = a b x b 1 f(x) = ax^{b} \implies f'(x) = abx^{b - 1} and f 1 ( x ) = 1 a ( 1 b ) x 1 b f^{-1}(x) = \dfrac{1}{a^{(\dfrac{1}{b})}} x^{\dfrac{1}{b}}

For x b 1 = x 1 b b 1 = 1 b b 2 b 1 = 0 x^{b - 1} = x^{\dfrac{1}{b}} \implies \boxed{b - 1 = \dfrac{1}{b}} \implies b^2 - b - 1 = 0 and

b > 0 b = 1 + 5 2 = ϕ b > 0 \implies b = \dfrac{1 + \sqrt{5}}{2} = \phi

For a b = 1 a ( 1 b ) = 1 a b 1 a b b = 1 ab = \dfrac{1}{a^{(\dfrac{1}{b})}} = \dfrac{1}{a^{b - 1}} \implies a^{b} b = 1 \implies a = ( 1 b ) 1 b a = (\dfrac{1}{b})^{\dfrac{1}{b}}

Checking:

f ( x ) = ( 1 b ) 1 b b x b 1 = b ( b 1 b ) x b 1 f'(x) = (\dfrac{1}{b})^{\dfrac{1}{b}} b x^{b - 1} = b^{(\dfrac{b - 1}{b})} x^{b - 1}

and

f 1 ( x ) = ( b 1 b ) ( 1 b ) x b 1 = b ( b 1 b ) x b 1 = f ( x ) f^{-1}(x) = (b^{\dfrac{1}{b}})^{(\dfrac{1}{b})} x^{b - 1} = b^{(\dfrac{b - 1}{b})} x^{b - 1} = f'(x) .

f ( x ) = ( ϕ 1 ) ϕ 1 x ϕ \therefore f(x) = (\phi - 1)^{\phi - 1} x^{\phi} and f 1 ( x ) = ϕ ( ϕ 1 ϕ ) x ϕ 1 f^{-1}(x) = \phi^{(\dfrac{\phi - 1}{\phi})} x^{\phi - 1}

The area A = 0 ϕ f 1 ( x ) f ( x ) d x = ϕ ( ϕ 1 ϕ ) ϕ x ϕ ( ϕ 1 ) ϕ 1 x ϕ + 1 ϕ 2 0 ϕ = A = \displaystyle\int_{0}^{\phi} f^{-1}(x) - f(x) \:\ dx = \dfrac{\phi^{(\dfrac{\phi - 1}{\phi})}}{\phi} x^{\phi} - \dfrac{(\phi - 1)^{\phi - 1} x^{\phi + 1}}{\phi^2}|_{0}^{\phi} =

ϕ ( ϕ 2 1 ϕ ) ϕ ϕ + 1 ϕ ( 2 ϕ + 1 ϕ ) \phi^{(\dfrac{\phi^2 - 1}{\phi})} - \dfrac{\phi^{\phi + 1}}{\phi^{(\dfrac{2\phi + 1}{\phi})}}

= ϕ ( ϕ + 1 1 ϕ ) ϕ ( ϕ 2 ϕ 1 ϕ ) = ϕ 1 = \phi^{(\dfrac{\phi + 1 - 1}{\phi})} - \phi^{(\dfrac{\phi^2 - \phi - 1}{\phi})} = \boxed{\phi - 1}

and from above f 1 ( ϕ ) = ϕ ( ϕ 1 ϕ ) ( ϕ ) ϕ 1 = f^{-1}(\phi) = \phi^{(\dfrac{\phi - 1}{\phi})} (\phi)^{\phi - 1} = ( ϕ ) ( ϕ 2 1 ϕ ) = ( ϕ ) ( ϕ + 1 1 ϕ ) = ϕ (\phi)^{(\dfrac{\phi^2 - 1}{\phi})} = (\phi)^{(\dfrac{\phi + 1 - 1}{\phi})} = \boxed{\phi}

f 1 ( ϕ ) A = ϕ ( ϕ 1 ) = 1 \implies f^{-1}(\phi) - A = \phi - (\phi - 1) = \boxed{1} .

Jon Haussmann
Apr 6, 2020

It's my problem. I reposted it. How are you doing ?

Rocco Dalto - 1 year, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...